How Does Water Availability Affect the Allocation to Bark in a Mediterranean Conifer? - Martín-Sanz, Ruth C.; San-Martín, Roberto; Poorter, Hendrik; Vázquez, Antonio; Climent, José (Frontiers in Plant Science, 2019)
Bark thickness is a key structural feature in woody plants in the protection against fire. We used 19 provenances of Pinus halepensis, an obligate-seeder species, in a replicated common garden at two environments contrasting in water availability to assess the interacting effects of site environment and population in the relative allocation to bark, expecting lower allocation at the drier site. Secondly, given the average fire frequency, we analysed whether trees reached the critical absolute thickness soon enough for population persistence via aerial seed bank. Our analyses indicated that trees at the moister site allocated a rather fixed quantity of resources independent of tree size, and almost all populations reached critical absolute bark thickness to eventually survive fire. In contrast, at the drier site allocation to bark reduced with tree size, and most populations did not reach the critical bark thickness. Populations from areas with higher fire frequency had thicker basal bark, while those from areas with severe droughts and short vegetative periods, had thinner bark. In conclusion, drought-stressed trees have a higher risk to die from fires before achieving reproduction and building a sufficient aerial seed bank.